PEMURNIAN BIOETANOL MENGGUNAKAN PROSES ADSORBSI DAN DISTILASI ADSORBSI DENGAN ADSORBENT ZEOLIT - Dewi Novitasari; Djati Kusumaningrum; Tutuk Djoko Kusworo (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Bioethanol is an alcohol substance which can be obtained by biomass fermentation process bymeans of Saccharomyces Cereviceae help. Adsorption is a separation process where thecomponents of a fluid phase moves to the absorbing surface of the solid (adsorbent). This researchaims to examine the process of bioethanol purificationusing adsorption and distillation process bythe influence of variations of the variables. In the distillation process produces ethanol conyentthat is not too high, so it needs to be atudied a process that can increase the purity of bioethanolwith distillation adsorption process. Bioethanol purification process using zeolite as adsorbentwith 4 variables change in the adsorption process, namely: the type of zeolite, stirring time,residence time, and heavy of zeolite. Whereas ondistillation adsorption process using 4 variableschange, namely: the type of zeolite, temperaturem weight of zeolite, and processing time. From theresults most effective process for ethanol purification is distillation adsorbtion process with zeolite4A adsorbent weighing 100 grams, the process temperature 78oC, processing time 50 minutes.Levels of ethanol produced was 98,42%.